#### Answer

$3x^{10}$

#### Work Step by Step

RECALL:
$\dfrac{a^m}{a^n} = a^{m-n}, a\ne0$
Divide the numerical coefficients then use the rule above to obtain:
$=3^{7-(-3)}
\\=3x^{7+3}
\\=3x^{10}$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$3x^{10}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.